Experimental Study on Compressive Strength of Ultrahigh Performance Concrete Prefabricated Wall Structure - Jianfeng Cao; Yunfei Dai; Liqiang Hu; Yu luo; Fang Long; Shiying Ding (Journal of Chemistry)
In order to study the influence of two parameters, height-thickness ratio and reinforcement ratio, on the compressive performance of prefabricated recycled concrete block-filled core walls, the author proposes a test method for the compressive strength of wall structures. In this method, 9 walls of dry and full-fill masonry are used, and the test measuring device and the arrangement of measuring points are designed to carry out the loading test. The results showed that reinforcement can significantly improve the axial compressive bearing capacity of the wall, but the out-of-plane displacement of the unreinforced wall is smaller than that of the reinforced wall. The larger the height-to-thickness ratio, the better the ductility of the reinforced core wall; the measured value of the axial compressive bearing capacity of the core-filled wall and the mean and coefficient of variation of the ratio to the standard calculated value were 1.49 and 0.13, respectively. The measured value is 34% to 68% higher than the standard calculated value. In conclusion, based on the test data and GB 50003–2011 “Code for Design of Masonry Structures,” the theoretical calculation formula of the compressive bearing capacity of the prefabricated recycled concrete block-filled core wall is given.